The impact of consumer preference factors on people willingness towards vehicle leasing program - Pan, Ying Qian (2022)
Vehicle leasing program is very common in the western countries, but the Malaysia vehicle leasing market was underdeveloped and few of the MNC companies has failed to penetrate the market. Majority of the population own a vehicle by obtaining loan from financial institution and make monthly payment. Malaysia public transport infrastructure was underdeveloped, this has made vehicle to become an essential need in daily life. Hence, this research studies on the vehicle leasing program that is available in the country and analyses the consumer preference factors that affect people willingness in vehicle leasing. The independent variables were as convenience, ownership, cost, and flexibility; the dependent variable was people willingness towards vehicle leasing. A questionnaire was distributed to collect the feedback of the people. In total 257 responses were collected, the data was analysed by descriptive statistics, Pearson correlation coefficient and multiple linear regression analysis. The results shown that there is a positive relationship in between independent variables and dependent variable, except for vehicle ownership, no significant relationship is identified. To make individual willing to lease a vehicle, the leasing providers should take the three deciding elements into consideration, which are convenience, cost, and flexibility.